Bus encoding for total power reduction using a leakage-aware buffer configuration. - Rao, R.R (IEEE Transactions on VLSI systems)
Power consumption, particularly runtime leakage, in long on-chip buses has grown to be an unacceptable portion of the total power budget due to heavy buffer insertion used to combat RC delays. In this paper, we propose a new bus encoding algorithm and circuit scheme for on-chip buses that eliminates capacitive crosstalk while simultaneously reducing total power. We utilize a buffer design approach with a selective use of high-threshold voltage transistors and couple this buffer design with a novel bus encoding scheme. The proposed encoding scheme significantly reduces total power by 26% and runtime leakage power by 42% while also eliminating capacitive crosstalk. In addition, the proposed encoding is specifically optimized to reduce the complexity of the encoding logic, allowing for a significant reduction in overhead which has not been considered in previous bus encoding work.